Competitive Advantage of Car100 Showroom Tanjung Pinang is Determined By Digital Marketing, Innovation and Service Quality With Intervening Customer Satisfaction. - Ade Kurniadi; Chablullah Wibisono; Nurhatisyah Nurhatisyah (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This study aims to determine the direct and indirect effect of digital marketing, innovation, service quality on competitive advantages through customer satisfaction of Car100 Showroow. This type of research uses quantitative research methods with primary and secondary data sources. The population in this study was 109 Civil Servants (PNS) who worked at the Bintan Regency Regional Secretariat office. In this study, data collection was carried out using the census method in which the entire population was taken as a sample. By using the census method, this study aims to obtain accurate and representative data from the entire existing population. This step will make it easier for researchers to analyze and describe the characteristics and events that occur in the population. This research uses Smart-Pls as a data processing tool. The results of this study, Digital marketing has a positive and significant influence on customer satisfaction. Innovation has a positive and highly significant influence on customer satisfaction. Service quality has a positive and highly significant influence on customer satisfaction. Digital marketing has a direct positive and significant influence on competitive advantage. Innovation has a negative but significant influence on competitive advantage. Customer satisfaction has a positive and highly significant influence on competitive advantage. Service quality has a positive and significant direct effect on competitive advantage. Digital marketing has a positive and significant indirect effect on competitive advantage through customer satisfaction as a mediating variable. Innovation has a positive and highly significant indirect effect on competitive advantage through customer satisfaction. Service quality has a positive and highly significant indirect effect on competitive advantage through customer satisfaction.